(σ,τ)-derivasi pada Ring Grup - Waluyo, Ridho; Faisol, Ahmad; Fitriani, Fitriani (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2025)
Derivations play a fundamental role in ring theory and have been extensively studied and generalized, including to (σ, τ)-derivations, which involve endomorphisms σ and τ. While many studies have focused on (σ, τ)-derivations in prime, semiprime, or commutative rings, explicit constructions and investigations of such derivations in group rings remain limited. This paper constructs several concrete examples of (σ, τ)-derivations on group rings and explores their algebraic properties. The approach provides systematic illustrations and characterizations of derivations in noncommutative ring structures based on groups, thereby contributing to the development of derivation theory in group ring contexts.